2010
DOI: 10.1097/ede.0b013e3181dec3a7
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Air Pollution and Vascular Damage in Young Adults

Abstract: Air pollution may accelerate arterial-wall stiffening in young adults. Small outcome variability and lack of residential mobility data may have limited the power to detect an effect on intima-media thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 39 publications
4
104
3
1
Order By: Relevance
“…23,24 An interim analysis 25 in MESA showed that exposure to a 2·5 μg/m 3 higher PM 2·5 concentration was associated with a 5 μm per year increase in intima-media thickness progression; the interim study used a different approach to image analysis, a less-developed approach to exposure estimation, and a much shorter period of follow-up. An observational study 26 within clinical trial data showed associations between PM 2·5 and intima-media thickness progression in some subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 An interim analysis 25 in MESA showed that exposure to a 2·5 μg/m 3 higher PM 2·5 concentration was associated with a 5 μm per year increase in intima-media thickness progression; the interim study used a different approach to image analysis, a less-developed approach to exposure estimation, and a much shorter period of follow-up. An observational study 26 within clinical trial data showed associations between PM 2·5 and intima-media thickness progression in some subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…A study of young adults in the Netherlands (Lenters et al, 2010) found no significant associations between either PM 2.5 mass or BC and vascular damage in a population-based cohort of those born between 1970 and 1973, who attended secondary school in Utrecht, the Netherlands, and who agreed to participate in the study. A subpopulation of never smokers showed significant associations with both PM 2.5 mass and BC.…”
Section: Epidemiological Studiesmentioning
confidence: 97%
“…Other sources of NO x include soil and lightning. NO 2 has been used as a marker for vehicle emissions and has thereby been associated with adverse human health effects (Brook et al, 2007;Jerrett et al, 2009;Clark et al, 2010;Lenters et al, 2010). In the province of Ontario, Canada, the government guideline exposure limit for NO 2 is 100 ppb averaged over 24 h and 200 ppb averaged over 1 h. Despite the association of NO 2 with adverse health outcomes, and its utility as a marker for traffic and/or combustion pollution, NO 2 monitoring networks remain sparse.…”
Section: Introductionmentioning
confidence: 99%